Moral Education and the Teacher Training Programme - G.H. Mukherjee, G.H. Mukherjee (Penerbit Universiti Sains Malaysia, 1980)
Because education is a human activity, it requires human agents to plan and carry out a complex series of programmes which constitute the total process of formal education. The key human agents are the teachers, whose role includes the transmission as well asthe transformation of the inherited culture and value system. Consciously or unconsciously, for better or for worse, they exert a powerful influence on the shaping of the future by virtue of their role as conservators and as change agents in the educational process. For this reason, the education of teachers constitutes the heart of the problem in social, economic and political development